Student Self Regulated Learning Strategy In Online Arabic Learning - Azkia Muharom Albantani; Ahmad Madkur; Abd. Rozak (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to describe the self-regulated learning strategy of students of the Arabic Language Education Program at UIN Antasari Banjarmasin in online Arabic lectures during the pandemic. This study used a qualitative method with an exploratory investigative approach to identify 100 students' self-regulated learning strategies to support learning Arabic from a distance. This study examines 4 (four) indicators in self-regulated learning strategies, namely Goal Setting, Environment Structuring, Task Strategies, and Time Management. The results showed that one of the goal-setting strategies, where students hope to master the elements of Arabic and have Arabic language skills, got the highest average score of 5.68 out of 6. While the time management, in which students benefitted from online learning as it is flexible in determining additional study time, got the lowest average score of 3.95 out of a scale of 6. This value still shows a positive trend which can be interpreted that those students have carried out self-regulated learning strategies well in online Arabic lectures